2017
DOI: 10.1515/cclm-2017-0865
|View full text |Cite
|
Sign up to set email alerts
|

Harmonization in laboratory medicine: more than clinical chemistry?

Abstract: Abstract:The goal of harmonizing laboratory information is to contribute to quality in patient care, ultimately improving upon patient outcomes and safety. The main focus of harmonization and standardization initiatives has been on analytical processes within the laboratory walls, clinical chemistry tests in particular. However, two major evidences obtained in recent years show that harmonization should be promoted not only in the analytical phase but also in all steps of the testing process, encompassing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…Therefore, establishment of an efficient network of regional clinical laboratories, involving those which are not directly challenged by the outbreak and where samples can be conveyed, is a feasible solution, provided that a straightforward regulation for specimen transportation and biosafety is set and monitored ( Figure 2). This, in turn, highlights an unavoidable need to place major efforts for allowing better and wider harmonization of laboratory results and information, encompassing both analytical and extra-analytical issues [26][27][28].…”
Section: Organizational Issuesmentioning
confidence: 99%
“…Therefore, establishment of an efficient network of regional clinical laboratories, involving those which are not directly challenged by the outbreak and where samples can be conveyed, is a feasible solution, provided that a straightforward regulation for specimen transportation and biosafety is set and monitored ( Figure 2). This, in turn, highlights an unavoidable need to place major efforts for allowing better and wider harmonization of laboratory results and information, encompassing both analytical and extra-analytical issues [26][27][28].…”
Section: Organizational Issuesmentioning
confidence: 99%
“…In the recent publications about harmonization in laboratory medicine, it has been emphasized that despite years of advances in laboratory quality, which has been primarily focused on the analytical phase, we are still struggling to harmonize significant areas of the total testing process, which includes areas such as reference ranges, report formats, decision limits and criteria for interpretation. 10 , 11 The practice of adding on tests is widespread in the UK; however, this survey has shown that significant variation exists in how this is performed and whether additional testing falls under reflex or reflective testing. Here, we aim to provide some discussion and proposals based on the various scenarios surveyed and the current evidence base around these topics.…”
Section: Discussionmentioning
confidence: 99%
“…An essential issue in this efforts to provide integrated and high quality information is represented by harmonization of clinical data. In particular, further efforts should be promoted to provide harmonization and standardization in laboratory medicine, not only in the analytical phase but also in all steps of the total testing process (76)(77)(78).…”
Section: Drawbacks Potential Solutionsmentioning
confidence: 99%